The Low Glutamate Diet Significantly Improves Pain and Other Symptoms in Veterans with Gulf War Illness. (29th May 2020) - Holton, Kathleen; Kirkland, Anna; Brandley, Elizabeth; VanMeter, John; Baraniuk, James
Abstract: Objectives: The objective was to examine if a low glutamate diet can reduce symptoms in Gulf War Illness (GWI), a multi-symptom chronic pain condition. Methods: Forty GW veterans were recruited from across the US. Baseline measures included assessment of symptoms, myalgic score, tender point count, and dolorimetry. Subjects were randomized to the low glutamate diet, or to a wait-listed control group, starting the diet one month later. Measures were evaluated post-diet, and then subjects were randomized to a double-blind placebo-controlled crossover challenge with monosodium glutamate (MSG)/placebo to assess whether symptoms return/worsen in each condition. Challenge data have not yet been un-blinded, and thus are not included in this abstract. Symptom scores were compared between those randomized to immediate dietary intervention versus wait-listed controls (independent t-tests). After everyone completed the 1-month diet, change scores were analyzed for the whole group (Wilcoxon Signed Rank tests). Improvement was defined as 'much' or 'very much' improved on the patient global impression of change (PGIC) score, and the effect size was calculated (Cohen's d) . Results: After 1-month, overall symptom number (mean (SD)) significantly differed between the diet group (11(6)) and the wait-listed controls (18(6)), P  = 0.0007. The diet had a very large effect size, d = 1.17, with no adverse effects reported. When comparing pre-post scores after all subjects followed the 1-month diet, the number of symptoms went from a mean(SD) of 21(5) at baseline to 12(6) post-diet, P  < 0.0001. The severity of remaining symptoms was also significantly reduced (all P  < 0.0001). Seventy-two % of subjects met the PGIC criteria for improvement. Highly significant improvements in pain measures were also observed for myalgic score ( P  < 0.0001), number of tender points ( P  < 0.0001), and average dolorimetry ( P  < 0.001). Conclusions: These striking results suggest that the low glutamate diet may be an effective treatment for chronic pain and symptoms associated with Gulf War Illness. Funding Sources: Department of Defense (DoD), US Army Medical Research Acquisition Activity, Office of the Assistant Secretary of Defense for Health Affairs through the GWI Research Program. Opinions, interpretations, conclusions and recommendations are those of the author and are not necessarily endorsed by the DoD.